Banking on Connectivity: Internet Exposure and Women's Financial Autonomy - Sagnik Kumar Gupta; Manini Ojha; Gaurav Dhamija (Global Labor Organization (GLO), 2025)
We examine whether women's exposure to the internet enhances their economic agency in India. Using nationally representative data and an instrumental variables strategy that exploits plausibly exogenous variation in district-level mobile tower density, we identify the causal effect of internet access on women's financial control and use of formal banks. We find that internet exposure increases women's overall financial autonomy by 10 percentage points. We document improvements in independent mobility, employment, and financial awareness which we consider potential mechanisms of our estimated effects. Disaggregated outcomes show higher likelihood that women have money of their own over which they full control, as well as increased ownership and active use of a bank account. Our results are robust to additional controls and a battery of sensitivity analyses. Heterogeneity analyses indicate that effects are concentrated among women with at least secondary education, and among those from historically disadvantaged social groups. Overall, our findings highlight the importance of digital connectivity in enhancing the usage of financial resources, with important implications for women's autonomy and participation in the formal economy.
Keywords: D13; G20; I31; J16; O12; 330; Internet Exposure; Mobile Tower Density; Financial Autonomy; Instrumental Variable; India